Exploring the Development of Reflective Practice Knowledge in Nursing Students - Zineb El Atmani (Journal of Research in Environmental and Science Education, 2025)
Reflective practice is a fundamental pillar of contemporary nursing education, crucial for developing competent, autonomous, and reflective practitioners. It empowers nursing students to critically analyze complex healthcare scenarios, make evidence-based decisions within their professional domain, and implement effective interventions both independently and as part of multidisciplinary teams. Reflective practice also bridges the gap between theoretical knowledge and practical application, fostering the critical thinking skills vital to delivering high-quality patient care. This study examines nursing students’ understanding of reflective practice and its integration into the curriculum at the Higher Institute of Nursing Professions and Health Technology (ISPITS) in Al Hoceima. A structured survey was administered to 100 ISPITS students to evaluate their perceptions and knowledge of reflective practice. The findings revealed notable ambiguities in students’ understanding of the concept, highlighting a lack of clarity regarding its objectives and methods. Furthermore, significant gaps were identified in the practical application of reflective practice within the educational framework. These challenges are exacerbated by constraints faced by instructors, such as limited resources, inadequate training in reflective teaching methods, and insufficient institutional support for the effective implementation of reflective practice. Despite these obstacles, instructors have made considerable efforts to diversify teaching methods and tools to foster student reflection, even in the absence of formal training in reflective practice. Their dedication underscores the critical need for targeted interventions. Recommendations include providing specialized training for instructors, integrating structured reflective activities into the curriculum, and cultivating an institutional culture that values and supports reflective practice. These strategies are essential to prepare nursing students to excel in dynamic healthcare environments, ensuring the delivery of safe, effective, and compassionate care.